Sistema Informático para la gestión de la Clínica Oral Home. - Esquivel García, Alba Wendalina (2018)
This research work was developed based on the problems that arise in the dentists of the Oral Home Clinic who are still recording the information of all their activities performed manually, or in flat text files using a computer, they are unaware that all this information must be well organized and arranged in a very clear manner so that they can use it at the right time without the need to have a lot of time to carry out the activities that take care of a patient. With the aim of developing a mobile application through the Android platform, for the integral management of the processes of the Oral Home clinic in the city of Quito. The development methodology that will be used in the realization of this project is using free and high technology tools such as Movile-D since this methodology is based on various technologies such as Rational Unified Process, Extreme Programming and Crystal Mehodologies, and its purpose is to try to get small development cycles quickly in small devices. Finally, in order to develop the proposal, the research line was established, Integral System for the Management of the Oral Home Clinic, where the entire process to be carried out fits, allowing the design of the proposed application, achieving a better optimization and standardization in the flow of information within each of the processes of user management, booking of medical appointments, administration of dentists, secretaries, creation of appointments. Through the implementation of this comprehensive management system could be streamlined the handling of appointments with which would save time and meet the requirements of patients and thus improve the service.